2020
DOI: 10.1016/s1473-3099(20)30086-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiological findings from 81 patients with COVID-19 pneumonia in Wuhan, China: a descriptive study

Abstract: Background A cluster of patients with coronavirus disease 2019 (COVID-19) pneumonia caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were successively reported in Wuhan, China. We aimed to describe the CT findings across different timepoints throughout the disease course.Methods Patients with COVID-19 pneumonia (confirmed by next-generation sequencing or RT-PCR) who were admitted to one of two hospitals in Wuhan and who underwent serial chest CT scans were retrospectively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

314
3,378
19
200

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,433 publications
(3,911 citation statements)
references
References 21 publications
(25 reference statements)
314
3,378
19
200
Order By: Relevance
“…Therefore, CT could be regarded as an efficient tool for the early detection and monitoring the dynamic evolution in the patients with COVID-19. 24 Our study has several limitations. Firstly, the sample size was relatively small.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, CT could be regarded as an efficient tool for the early detection and monitoring the dynamic evolution in the patients with COVID-19. 24 Our study has several limitations. Firstly, the sample size was relatively small.…”
Section: Discussionmentioning
confidence: 91%
“…Laboratory results were considered as auxiliary information to diagnose COVID-19 infection. 5,7 In our hospital, there were 14 cases confirmed COVID-19 infection. Of 14 patients, white-cell count was tended to be normal in 12 patients (85.71%), lymphocyte (8/14, 57.14%) and monocyte (9/14, 64.29%) percentage had a tendency to decrease.…”
Section: Chest Ct and Rt-pcr For Detection Of Covid-19 Infectionmentioning
confidence: 90%
“…But it doesn't mean that the abnormalities of CT images could be observed in the COVID-19 infection while the initial RT-PCR is positive or negative. [3][4][5][6] Therefore, even though chest CT plays a key role in detection or diagnosis of COVID-19 infection, however, chest CT examination and RT-PCR results should be mutual verification for precise diagnosis in the patient suspected COVID-19 infection.…”
Section: Chest Ct and Rt-pcr For Detection Of Covid-19 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the studies demonstrated that the CT findings were typical signs for diagnosis at different stages of COVID-19 pneumonia. 3,4 Particularly, ground glass opacities (GGO) and consolidation were the principal manifestation in the CT images (CT scans before onset of symptoms or CT scans done ≤ 1 week after symptom onset), and GGO was decreased with increasing the stages of COVID-19 pneumonia. However, the consolidation or GGO mixed consolidation increased, and reticular was also observed in the later stages (scan > 1 week after symptom onset).…”
mentioning
confidence: 99%